Onclarity Human Papillomavirus Extended Genotyping in the Management of Cervical Intraepithelial Neoplasia 2+ Lesions. Issue 1 (January 2019) - Bottari, Fabio; Iacobone, Anna Daniela; Boveri, Sara; Preti, Eleonora Petra; Franchi, Dorella; Mariani, Luciano; Preti, Mario; Landoni, Fabio; Passerini, Rita; Sandri, Maria Teresa
Abstract : Objective: Many methods are available today for human papillomavirus (HPV) testing; they differ for technology, targets, and information on the genotypes detected. In this study, we evaluated the performance of the Onclarity HPV assay in detection and follow-up of cervical preneoplastic lesions. Materials and Methods: One hundred sixty-seven women referred to the European Institute of Oncology, Milan, for treatment of cervical lesions were enrolled. We investigated the utility of Onclarity extended genotyping HPV test in the management of cervical intraepithelial neoplasia (CIN) 2+ preneoplastic lesion. Results: At baseline, the concordance was 92% (150/163) between Onclarity and Hybrid Capture 2 (HC2) and 93% (142/152) between Onclarity and linear array, respectively. At follow-up, the concordance between Onclarity and HC2 was 80%. Seven women relapsed: 6 had persistence of the same genotypes and 1 patient tested negative not only with Onclarity but also with HC2 for the presence of a low-risk genotype in the sample. Conclusions: This study showed that the evaluation of the HPV genotype persistence may represent a valid option to monitor patients treated for CIN 2+ lesions, because relapses were detected only in patients with persistence of the same genotype detected at baseline.